2002
DOI: 10.1007/s11886-002-0105-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, left ventricular hypertrophy, and sudden death

Abstract: Left ventricular hypertrophy (LVH), a form of end-organ damage in hypertension, is associated with increased incidence of sudden cardiac death (SCD). This review explores the possible mechanisms behind this phenomenon. SCD in LVH could be thrombotic/ischemic or arrhythmic (eg, myocardial ischemia, even in the absence of significant coronary artery disease, may be one important factor). Abnormalities of flow-mediated dilatation, endothelial function, and a hypercoagulable state are well-observed abnormalities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 90 publications
(80 reference statements)
0
31
0
1
Order By: Relevance
“…[16][17][18] Indeed, the identification of LVH in patients with MHT is of great importance, in view of the relationship between LVH and arrhythmias, as well as sudden death. 19,20 These arrhythmias could in part explain the increased mortality seen in untreated MHT patients, 3 or in subjects where the treatment may be suboptimal. 7 The presence of severe LVH in our patients suggests that even in the undiagnosed patients, the hypertension could have been long standing but undetected.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Indeed, the identification of LVH in patients with MHT is of great importance, in view of the relationship between LVH and arrhythmias, as well as sudden death. 19,20 These arrhythmias could in part explain the increased mortality seen in untreated MHT patients, 3 or in subjects where the treatment may be suboptimal. 7 The presence of severe LVH in our patients suggests that even in the undiagnosed patients, the hypertension could have been long standing but undetected.…”
Section: Discussionmentioning
confidence: 99%
“…25 Significant LVH is a common feature of uremic cardiomyopathy, with 60% to 80% of patients with ESRD commencing dialysis while showing echocardiographic evidence of LVH. 26 In addition to systemic hypertension, both as a common cause of ESRD and as a consequence of it, other factors unique to ESRD, such as hyperparathyroidism, high cardiac output due to anemia and arteriovenous fistula, and activation of the neuroendocrine systems, contribute to this high incidence of LVH.…”
Section: Lvh and Risk Of Scd In Dialysismentioning
confidence: 99%
“…4 The development of hypertension and its relationship to CVD is multifactorial and likely includes both environmental and physiological/genetic components, including endothelial dysfunction, subendocardial fibrosis, and left ventricular hypertrophy (LVH). 5,6 The relationship of LVH to cardiac death 6,7 is of particular importance in blacks because of the higher prevalence of hypertension associated LVH in this ethnic group. Echocardiographic data from the Coronary Artery Risk Development in Young Adults study showed that LV mass was higher in blacks than in whites and correlated with systolic blood pressure.…”
Section: Selected Traditional Risk Factors Hypertensionmentioning
confidence: 99%